«Las mil caras de la bella malmaridada» nos autores do teatro português do século XVI (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2024)
Most of today's 16th-century Portuguese theatre readers do not notice the presence of more or less reworked verses from old romances in the theatrical production of authors such as Gil Vicente, António Prestes, Francisco de Sá de Miranda and Jorge Ferreira de Vasconcelos. Since many readers are unaware of it, the reading of the pieces is greatly impaired, as this technique creates poetic, semantic and ideological effects that are part of the new literary text. This research takes a further step in the studies of this phenomenon of literary creation, which is quite frequent in Spanish and Portuguese plays, focusing on the application of verses from the novel "La bella malmaridada" in dramatic works by 16th century Portuguese authors.
Keywords: ancient romances; la bella malmaridada; five century theatre